REASON FOR HOSPITAL ADMISSION IN PEDIATRIC WARD OF AN INDONESIAN RURAL HOSPITAL IN 2023 - Rofiqoh, Siti; Utami, Susri; Paradisi, Firman; Ristanti; Ersila, Wahyu (Fakultas Kedokteran Universitas Sriwijaya, 2024)
This study aims to determine the number of pediatric patients hospitalized at one rural hospital in Pekalongan Regency, Central Java, during 2023. This research design uses a descriptive cohort study with a cross-sectional approach. The research data was obtained from the hospital's Electronic Medical Records or E-RM. This study's results show that 2,731 children were being treated at Kajen Regional Hospital during 2023, with length of stay varying from 1 to 20 days. The most common reasons for hospitalization were fever, nausea, vomiting, cough and cold, febrile seizures, diarrhea, and shortness of breath. During 2023, there were 57 cases of death, and the three highest causes of death were fever: 23(40%) cases, seizures: 13(23%) cases, and shortness of breath and cough: 13(23%) cases. The results of this research can be used to determine priorities for preventive health programs to reduce hospitalization and child mortality rates. The plausible actions to respond to this situation are improving the vaccination program uptake, sanitation, and nutrition education by involving local leaders and community organizations to reduce the detrimental effect of fever, seizure, and respiratory disease on children.